2015
DOI: 10.1089/lap.2014.0507
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Preoperative Oral Acetazolamide and Intraperitoneal Normal Saline Irrigation for Reduction of Postoperative Pain After Laparoscopic Cholecystectomy

Abstract: Intraperitoneal normal saline irrigation is more effective than acetazolamide in reducing postoperative visceral pain after laparoscopic cholecystectomy and has significant opioid-sparing effect. However, its effect on shoulder pain is comparable to that of acetazolamide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 13 publications
0
16
1
Order By: Relevance
“…It is possible that tissue acidosis, an important side effect of acetazolamide, be responsible for the higher frequency of diffuse abdominal pain and referred shoulder pain in group A in the recovery room. Bala et al (2015) observed that visceral pain scores were significantly lower while resting, coughing, and moving at 2, 4, 6, 12, and 4 hours postoperatively (16). The effect of a single dose of acetazolamide is known to last for 4-6 hours.…”
Section: Discussionmentioning
confidence: 97%
“…It is possible that tissue acidosis, an important side effect of acetazolamide, be responsible for the higher frequency of diffuse abdominal pain and referred shoulder pain in group A in the recovery room. Bala et al (2015) observed that visceral pain scores were significantly lower while resting, coughing, and moving at 2, 4, 6, 12, and 4 hours postoperatively (16). The effect of a single dose of acetazolamide is known to last for 4-6 hours.…”
Section: Discussionmentioning
confidence: 97%
“…Postoperative shoulder pain occurs in about 30%–45% of laparoscopic patients [ 8 9 ] and irrigation with normal saline has been shown to reduce the incidence of postoperative shoulder tip pain at 8, 16, and 24 hours after the surgery by 35%, 15%, and 10%, respectively [ 5 ]. One study reported that the infiltration of local anesthetics in the postoperative trocar site was not effective in reducing parietal pain [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…One study reported that the infiltration of local anesthetics in the postoperative trocar site was not effective in reducing parietal pain [ 10 ]. Meanwhile, another study reported that the preoperative administration of carbonic anhydrase inhibitors such as acetazolamide was effective in reducing postoperative pain, and suspected that postoperative pain is caused by the production of carbonic acid and acidification of the abdominal cavity from CO 2 insufflation [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Significant and persistent alterations in both the periphery and central nervous system have been documented in animals subjected to intestinal inflammatory damage [4,22]. Although it is not known whether a dysregulation of CA activity occurs in these processes, the commonalities existing between chronic visceral pain and neuropathic pain [4,23] make CA an interesting target to investigate in the search for new therapies for abdominal pain relief in patients affected by IBD.…”
Section: Introductionmentioning
confidence: 99%